The Role of the Stock Market and the Banking Sector in the Iranian Economy: Evidence from Time Series Data, 1967-2009 - Athari, Alireza (Eastern Mediterranean University (EMU), 2011)
ABSTRACT: This thesis empirically investigates the relationship between the financial development and economic growth during the period between 1967- 2009 for the Iranian economy. In the light of exogenous modelling framework, the ‘Augmented Solow’ regression model is employed whether the financial or banking system stimulates the process of economic growth. The Ordinary Least Square (OLS) technique is applied to test the determinants of financial development which may have an impact on the Iranian economic growth. Based on the empirical results estimated, explanatory power supports the view that financial sector can be a good promoter of domestic economy in both long and short run. Additionally, stock market prices (volatility) have a negative influence on the Iranian output and suggest that volatility in stock prices may reflect economic ambiguity. Banking sector indicator was also found that it is so effective in the shortrun period. Keywords: Economy growth, OLS Analysis, Stock market, Banking system, Iranian economy. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Yapılan çalışma Ampirik olarak İran ekonomisindeki bankacılık ve menkul kıymetlerin Borsanın rolünü ölçmektedir. Bu rolü ölçerken ekonomik büyümenin borsa stok değerleri, stok fiyatlarının ve yerel banka kredilerinin ne kadar anlamlı olup olmadığına bakar. En Küçük Kareler tekniği kullanılarak Solow büyüme modeli üzerinden yıllık verileri alınarak 1967-2009 arası dönem için finansal politikalarının rolünü ölçmeye çalışır. Çalışma, aynı zamanda kullanılan Solow modelinin anlamlılığını da ortaya koymaya çalışıyor. Elde edilen ampirik sonuçlar ışığında, borsanın İran ekonomisi üzerinde önemli rol oynadığı gözlenmektedir. Stok fiyatlarının (dalgalanmanın) ekonomi üzerinde olumsuz bir etkisi görülmemektedir. Ayrıca, İran ekonomisinde, bankacılık sektörü ise kısa dönemde etkili bulunmuştur. Anahtar kelimeler: Ekonomik büyüme, En küçük kareler yöntemi, Borsa, Bankacılık, İran ekonomisi.
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2011. Supervisor: Assoc. Prof. Dr. Sami Fethi.
Keywords: Business Administration; Stock Exchanges - Iran; Financial Services Industry - Iran; Economic Growth - OLS Analysis - Stock Market - Banking System - Iranian Economy